VP 2021
DOI: 10.20517/2574-1209.2020.97
|View full text |Cite
|
Sign up to set email alerts
|

A revised stent-retriever anchor technique to obtain the distal access through a large or giant aneurysm

Abstract: Endovascular treatment of brain aneurysms with flow diverter device can be technically difficult. Obtaining distal access through the wide neck of a large or giant aneurysm may be challenging and sometimes the microcatheter needs to be looped inside the aneurysm. However, the inability to resolve this loop and to straighten the microcatheter can preclude flow diverter placement. This brief report presents four cases of large/giant aneurysms treated with flow diverter device, in which our innovative stent-retri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…The microcatheter tip in the distal parent vessel may be pulled back into the aneurysm dome when attempting to straighten the loop for stent delivery. 2,19 In 2007, Cekirge et al described a balloon anchoring technique in which a Hyperform balloon catheter (Medtronic) was inflated in the distal parent vessel while the wire was gently retracted and the loop straightened. 21 Other balloons have been used for similar techniques, including the Sceptor XC (Microvention Terumo) and the Gateway balloon catheter (Stryker Neurovascular) 1,8 While the use of a balloon may provide adequate support, drawbacks include temporary occlusion of flow, over- straightening of curved segments and potential vessel rupture.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The microcatheter tip in the distal parent vessel may be pulled back into the aneurysm dome when attempting to straighten the loop for stent delivery. 2,19 In 2007, Cekirge et al described a balloon anchoring technique in which a Hyperform balloon catheter (Medtronic) was inflated in the distal parent vessel while the wire was gently retracted and the loop straightened. 21 Other balloons have been used for similar techniques, including the Sceptor XC (Microvention Terumo) and the Gateway balloon catheter (Stryker Neurovascular) 1,8 While the use of a balloon may provide adequate support, drawbacks include temporary occlusion of flow, over- straightening of curved segments and potential vessel rupture.…”
Section: Discussionmentioning
confidence: 99%
“…Giant aneurysms present unique challenges for achieving and maintaining access, including unfavorable angles between the inflow and outflow tracts, flow characteristics, and wide or complex necks. 2,6,7 Previously proposed techniques to maintain access while intra-aneurysmal looping are reduced or while the necessary larger catheters are advanced include balloons, 1,7,9,10 detachable coils, 2 stents, 6,1116 microwires, 17 stent retrievers, 18,19 and the rapid pull-back technique. 20 In this study, the results suggested that the Stabilizer could be used for multiple techniques while treating a giant aneurysm, including straightening of intra-aneurysmal looping, exchange for a stent delivery catheter, and advancement of an intermediate catheter.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations